Assignment of Reviewers and Litdimas Assessment Process on Sirip UPN “Veteran” East Java - Chrystia Aji Putra; Ronggo Alit (Nusantara Science and Technology Proceedings)
LPPM is an institution that manages research and community service activities at University of Pembangunan Nasional “Veteran” Jawa Timur. Research and community service management activities in universities are accommodated by a system that regulates the research and community service activities. The big system is called SIRIP (Sistem Informasi Penelitian dan Pengabdian Masyarakat) that build since 2016. This year we build sub system from Sirip that called SIVENI (Sistem Verifikasi dan Penilaian Litdimas). This system can also display report information to its users. Purpose of this research is to create a system that is capable to facilities LPPM for assignment of reviewers and assessment process on SIRIP UPN "Veteran" Jatim. In this system, litdimas proposal documents are uploaded by lecturer. Furthermore, LPPM as manager has duty to verify the proposal document. LPPM appointed several lecturers as reviewers. Reviewers give grades on proposals uploaded by lecturers. This research is expected to provide solutions for LPPM in proposal verification and proposal assessment activities in research and community service that can be used routinely or continuously. Final result of this system is give ranking of proposals submitted by lecturers, so that this becomes data for LPPM in determining which proposals for litdimas which are given funding.